Worldview and the Construction of Economics: Secular and Islamic Tradition - Hafas Furqani (Universitas Darussalam Gontor, 2018)
Economics as a system of thought and body of knowledge is constructed based on certain philosophical foundations derived from a particular worldview. The term worldview, which originated from the German Weltanschauung (composed of Welt, ‘world’, and Anschauung, ‘view’ or ‘outlook’) refers to a world perception, or the concept and framework of ideas through which human interprets the human life and world. The term worldview, in general, refers to belief, doctrine, perspective and values in the sense that it supplies views, assumptions and images of how to perceive things. The worldview which is the perspective in understanding the existence and realities decorates the scientifc atmosphere, its direction as well as objectives. The worldview is also fundamental in supporting the development of a science and its progress. Mainstream economics is developed from the foundation of Secular Worldview which is characterized as materialist (excluding the metaphysics), reductionist (reducing the epistemological basis on positivism with atomistic perspective) and individualist (isolating individual from society). Islamic economics, on the other hand, is developed on the basis of Islamic worldview. The Islamic worldview is claimed to be more comprehensive, integrative and holistic in nature. This would make Islamic economics having a potential to answer the shortcoming found in conventional economics. The paper would explore the nature of worldview in Secular and Islamic tradition and its implications in developing discipline of economics and Islamic economics. The paper also seeks to develop some foundations for Islamic economics to be a distinct discipline.